Business communication : a problem-solving approach - Rentz, Kathryn; Lentz, Paula; Getchell, Kristen M. (India : McGraw Hill LLC, 2020)
"The goal is to coax students out of their comfort zones into a problem solving mindset while giving them the tools they need to make good communication decisions"--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Business communication